(untitled) (Jurnal AbdiMas Nusa Mandiri, 2026)
Environmental safety and order are important aspects of creating a harmonious and prosperous community life. Environmental Security Posts (Pos Kamling) play an important role as a community-based security system in maintaining order and preventing crime. However, residents in RT. 17, Sukamulya Village, Sematang Borang District, Palembang City are facing the problem of the increasing number of vehicle theft cases parked in their home yards. Therefore, this community service activity is carried out with the aim of designing and building a neighborhood watch post as a solution to improve environmental security. The methods used include field surveys, direct observation, and interviews with RT officials and local residents to collect relevant data and information. The results of this service include the preparation of Pos Kamling planning documents, including the calculation of the Budget Plan (RAB), as well as the physical construction of the post until it is ready for use. Beside being a security monitoring center, the neighborhood watch post also serves as a means of social interaction that can strengthen relationships between residents. A Pos Kamling management unit was established after the activity to carry out the patrol SOP, supply the duty schedule, oversee the fast reporting channel, and accept the transfer of DED, RAB, and SOP papers as operational instructions.